(untitled) (Research, Society and Development, 2022)
Instrumental texture profile analysis reproduces the chewing action and texture-related parameters. This, together with the sensory texture profile, allows the obtaining of representative results, characterizing the product under study in a more precise way. Therefore, this work aimed to evaluate the sensory and instrumental texture characteristics of gluten-free buttery biscuits with different proportions of carrot stems and leaf flour (CSLF). From the instrumental texture analysis and the texture profile by the Temporal Dominance of Sensations method, the results showed that the biscuits presented good instrumental quality. The hardness did not differ among the treatments studied, which shows that the increase in the concentration of CSLF did not interfere with this parameter, allowing the addition of higher concentrations of flour in the biscuits. The data from the Temporal Dominance of Sensations method showed positive attributes for the texture of biscuits with a higher concentration of flour, with the main dominant sensations being: crunchiness and low adhesiveness. The cookies showed good sensory quality, constituting a practical, affordable and healthy food alternative to serve the celiac public.